Representation of 212 rallies in the Jakarta Post articles: A hybridity of CDA and SFL analysis - Siti Sarah Fitriani; Rizki Ananda; Andi Muhammad Irawan; Iskandar Abdul Samad; Sukardi Weda (Studies in English Language and Education, 2021)
For decades, newspapers have become a daily need for people across the globe to update information. There is a tendency of the people to believe in the news published in newspapers, for media is considered neutral. In Indonesia, 212 rallies are the events that were widely reported as headlines for weeks by national and international newspapers. This study showcases the brief portrait of The Jakarta Post representations on the 212 rallies by its use of linguistic properties, to see whether The Jakarta Post is impartial in delivering the news. This study employs Critical Discourse Analysis (CDA) strategies and applies the analytical tools drawn from Systemic Functional Grammar (SFG). The data were taken from sixteen 212 rallies related news, including seven headlines, collected from The Jakarta Post archives. The result of this study reveals that by using transitivity and conceptual metaphor, The Jakarta Post tends to stand on the side of the one being protested, and oppose the rallies. This finding suggests newspaper readers to read the information in newspapers more critically, to understand the use of lexicon as well as the structure of sentences to conclude the right interpretation of the news and to realize the representation. By doing so, newspaper readers will not simply accept the news they read.